2019
DOI: 10.1016/j.celrep.2019.04.064
|View full text |Cite
|
Sign up to set email alerts
|

Functional Dominance of CHIP-Mutated Hematopoietic Stem Cells in Patients Undergoing Autologous Transplantation

Abstract: Highlights d Autologous stem cell transplantation promotes the expansion of mutant blood clones d CHIP-mutated human stem cells engraft long term and dominate blood reconstitution d Neutrophil reconstitution post-transplantation is delayed in patients with CHIP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 36 publications
1
37
0
5
Order By: Relevance
“…Furthermore, this research may also be important for informing HCT survivors and their caregivers as they consider plans for long-term surveillance and follow-up. A recent study of 81 patients undergoing autologous HCT found that CH mutations present before HCT were more likely to dominate blood reconstitution over wild-type hematopoietic stem cells after HCT [21], leading to an increased future risk of CH-associated complications in survivors. Therefore, information on CH status (either before or after HCT) may allow for implementation of more frequent screening intervals and management of modifiable risk factors in at-risk individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this research may also be important for informing HCT survivors and their caregivers as they consider plans for long-term surveillance and follow-up. A recent study of 81 patients undergoing autologous HCT found that CH mutations present before HCT were more likely to dominate blood reconstitution over wild-type hematopoietic stem cells after HCT [21], leading to an increased future risk of CH-associated complications in survivors. Therefore, information on CH status (either before or after HCT) may allow for implementation of more frequent screening intervals and management of modifiable risk factors in at-risk individuals.…”
Section: Discussionmentioning
confidence: 99%
“…CHIP may contribute to altered transplant outcomes and the development of DDL after both autologous and allogeneic HSCT ( Table 1 ). Autologous transplantation can facilitate expansion of HSPC clones containing CHIP-associated mutations ( Ortmann et al., 2019 ). These HSPCs demonstrate long-term engraftment and reconstitute the blood cell lineages.…”
Section: Main Textmentioning
confidence: 99%
“…CHIP patients exhibited longer neutrophil reconstitution, longer periods of hospitalization, and prolonged neutropenia. Clones carrying these preleukemic mutations can be detected years before disease onset and expand in response to transplantation ( Berger et al., 2018 ; Ortmann et al., 2019 ). The stress of transplantation has been proposed to drive expansion of HSPCs containing CHIP-associated mutations, implicating factors in the transplant environment in the modulation of HSPCs containing CHIP-associated mutations ( Ortmann et al., 2019 ).…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15][16] Moreover, in patients with CH, highdose conditioning regimens as part of treatment with ASCT have been shown to provide a proliferative advantage for mutated cell clones. 17 The impact of individual mutations in malignant transformation is still being investigated. However, it has become evident that mutations in both DNMT3A and TET2 can be detected in a large fraction of the healthy adult population 18 ; individually, these clones often display little to no clonal evolution over time and are associated with a lower increase in risk of developing myeloid neoplasms compared with mutations in TP53, IDH1/2, and spliceosome genes.…”
Section: Introductionmentioning
confidence: 99%